Textbook on international human rights - Smith, Rhona K.M. (Oxford : Oxford University Press, 2014)
Global in coverage, the sixth edition of Textbook on International Human Rights provides a concise, wide-ranging introduction for law students new to the subject. It considers historical factors, the work of the UN, regional systems, and a variety of substantive rights.
Introduction -- Historical background -- The United Nations -- The International Bill of Human Rights -- The United Nations : organizational structure -- Regional protection of human rights -- Europe -- The Organization of American States -- The African Union -- Monitoring, implementing, and enforcing human rights -- Substantive rights : general comments -- Equality and non-discrimination -- The right to life -- Freedom from torture : cruel, inhuman, and degrading treatment or punishment -- The rights to liberty of person -- Equality before the law : the right to a fair trial -- The right to self-determination -- Freedom of expression -- The right to work -- The right to education and human rights education -- Minority rights -- Rights for specific categories of persons -- Looking to the future.
Includes bibliographical references and index.
Keywords: Human rights